Improving visibility to archival collections - Balta, Kyriaki; Yiannoukakou, Aikaterini (Qualitative and Quantitative Methods in Libraries, 2019)
The National Theater of Norther Greece collection held by Historical Archives of Macedonia is used as a paradigm of an archival collection records enrichment program using Prown‘s model for item study and University of Calgary‘s model for Digital Collection Process in compliance with IFLA‘s Guidelines for Digitization Projects in order to increase the collection‘s access and its understanding in terms of cultural history.